COMPARISON OF THE MTT AND ALAMAR BLUE ASSAY FOR IN VITRO ANTI CANCER ACTIVITY BY TESTING OF VARIOUS CHALCONE AND HIOSEMICARBAZONE DERIVATIVES - HITESH D PATEL; ANURAG D ZAVERI; DILIP N ZAVERI; SAAVANI SHAH; ANKITA SOLANKI (International Journal of Pharma and Bio Sciences, 2013)
The MTT assay was compared with the Alamar Blue assay for in vitro anti cancer activity by testing of various Thiosemicarbazone and Chalcone derivatives on various human tumor cell lines. The Alamar Blue assay provided a better linearity with a cell number and a higher sensitivity, and its activity was not cell line dependent. In contrast to the MTT assay, Alamar Blue assay showed the convenience in successive observations and more accurate results. In our case, with thiosemicarbazone and chalcone derivatives two variables, sensitivity and colorimetric linearity with cell number were studied.